Tracing Identity: The Socio-Cultural Transformation of the Akit Tribe of Bengkalis in the Era of Globalization - M. Khairul Arwani; Nurangdini Zaenab Djahamao; Ilham Utama Yazid; Khotibul Umami; Sarah Afifah Afifah (UIN Imam Bonjol Padang, 2024)
The Akit tribe in Bengkalis has undergone significant socio-cultural transformations in the era of globalization. This study explores the complex processes through which the Akit community navigates changes in their identity, traditions, and social structures. The research examines the impact of global influences on local customs by investigating how external pressures and internal dynamics have reshaped the tribe's cultural landscape. Through a comprehensive analysis of historical and contemporary data, the study highlights the resilience and adaptability of the Akit people in preserving their heritage while integrating new cultural elements. The findings contribute to a broader understanding of the impact of globalization on indigenous communities, offering insights into the challenges and opportunities faced by the Akit tribe in maintaining their cultural identity in a rapidly changing world. Additionally, this research contributes to academic literature by providing new perspectives on cultural adaptation, sharpening the discourse on cultural sustainability in the modern era, and offering practical recommendations for policymakers in designing strategies that support the preservation of local cultures amidst the currents of globalization. The study's contributions are significant in fostering a deeper appreciation of the delicate balance between cultural preservation and adaptation, ensuring that the unique cultural identity of the Akit tribe is not lost but rather enriched through the thoughtful incorporation of global influences. By examining the Akit tribe's experiences, this research underscores the importance of culturally sensitive approaches in policy-making and highlights the role of indigenous knowledge in shaping sustainable development pathways.